2003
DOI: 10.1021/bc034069i
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Human Melanoma Targeting Properties of Radiolabeled α-Melanocyte Stimulating Hormone Peptide Analogues

Abstract: The purpose of this study was to evaluate the human MC1 receptor-mediated melanoma targeting properties of two metal cyclized alpha-MSH peptide analogues, (188)Re-(Arg(11))CCMSH and (188)Re-CCMSH. Initially, the presence and density of the MC1 receptor were determined on a bank of human melanoma cell lines. All eight human melanoma cell lines tested in this study displayed the MC1 receptor at a density of 900 to 5700 receptors per cell. Receptor affinity and biodistribution properties of (188)Re-(Arg(11))CCMSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 37 publications
1
83
0
Order By: Relevance
“…The IC 50 values of DOTA-CycMSH and DOTA-GlyGlu-CycMSH were determined by using methods described previously (8). B16/F1 cells were harvested and seeded into a 24-well cell culture plate (5×10 5 In-DOTA-GlyGluCycMSH was injected into each mouse through the tail vein.…”
Section: In Vitro Competitive Binding Assaymentioning
confidence: 99%
“…The IC 50 values of DOTA-CycMSH and DOTA-GlyGlu-CycMSH were determined by using methods described previously (8). B16/F1 cells were harvested and seeded into a 24-well cell culture plate (5×10 5 In-DOTA-GlyGluCycMSH was injected into each mouse through the tail vein.…”
Section: In Vitro Competitive Binding Assaymentioning
confidence: 99%
“…Due to their small size, peptides are also ideal for multiple modifications of nanoparticle constructs and generation of pluripotent nanoparticles. 38 Moreover, α-MSH binds to melanocortin receptors and, in particular, is a potent agonist of the melanocortin type 1 receptor (MCR1, overexpressed by many melanoma cells 39 ) and binds to MCR1 with high affinity (IC 50 0.21 nmol/L). 40 Importantly, more than 80% of human metastatic melanoma samples have been found to display MCR1.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported the MC1R expression ranges from several hundred to around 10,000 receptors per cell [29]. In 2003, Miao et al, reported that MC1R receptor expression ranged from nine hundred (1.49 fmol/million SKMEL28 cells) to around six thousand (9.46 fmol/ million TXM13 cells) receptors per cell on human melanoma cells [30], enabling the use of radiolabeled α-MSH peptide analogs as specific melanoma diagnostic and therapeutic agents.…”
Section: -[ 18 F]fluoro-2-deoxy-d-glucose ([ 18 F]fdg)mentioning
confidence: 99%